SLOPE STABILIZATION ON CHALKOUTSI – DILESI ROAD, AT PIGADAKIA LOCATION, ATTICA PREFECTURE - Mourtzas, N. D.; Symeonidis, K.; Passas, N.; Alkalais, E.; Kolaiti, E. (Bulletin of the Geological Society of Greece, 2010)
A series of ongoing landslides occurred at the steep coastal slopes at Pigadakia location, on the road connecting Chalkoutsi and Dilesi towns, at NE Attica. These landslides caused severe disruption on local traffic. Engineering geological study revealed the local geological conditions and the complex mechanism of the landslides. Site is located on the Neogene deposits composed mainly by layers of sandy or silty clays, marly clays with thin layers of conglomerates. Multiple landslides occurred on the steep costal slopes at a length of 280m parallel to the coast line. On the upper slopes which are composed by loose clayey materials typical circular failures occurred while on the lower ones, composed by hard clays and marls, discontinuities delineate failures under the weathering influence of sea waves. Six boreholes were drilled with piezometers and inclinometers installed in order to investigate the progress of the failures. The stabilization of the upper slopes included the use of soil nails covered with geocells. The lower slopes stabilization included the protection from sea wave erosion by covering slopes with a rock fill embankment.